(untitled) (Nativa, 2014)
Esta pesquisa objetivou realizar uma avaliação técnica de um sistema de cabos aéreos, utilizado na extração de madeira de eucalipto em região montanhosa. Os dados da pesquisa foram coletados no Vale do Rio Doce no Leste do Estado de Minas Gerais. A análise operacional do cabo aéreo relacionou um estudo de tempos e movimentos, onde a operação de extração foi subdividida nas seguintes fases: descida do cabo principal, engate, arraste, posicionamento das árvores na estrada, desengate, empilhamento das árvores, deslocamento do trator e interrupções. Para análise dos dados utilizou a Análise de Variância e o teste de Tukey ao nível de 5% de significância, seguido de uma regressão linear simples. Os resultados demonstraram que a atividade que consumiu o maior tempo do ciclo operacional foi a montagem do cabo principal nas árvores, com 35,8% do tempo total. O menor tempo gasto foi relativo às pausas dentro do talhão com cerca de 4% do tempo total da operação. A produtividade média do cabo aéreo variou de 10,2 à 115,3m³cc.he-1. Pela análise de regressão, a produtividade do cabo aéreo na extração de madeira em região montanhosa foi influenciada pelo volume do feixe de madeira, tempo do ciclo operacional e distância de extração. Palavras-chave: Colheita florestal; Mecanização Florestal; Rendimento Operacional. OPERATIONAL ANALYSIS OF EXTRACTION WITH CABLES AIR IN EUCALYPTUS FOREST ABSTRACT This work aimed to make a technical assessment of an overhead wires system used in the eucalyptus wood extraction on mountainous region. The survey data were collected in Vale do Rio Doce, eastern of Minas Gerais state. The operational analysis of cable related with study of time and motion, where the extraction operation was divided into phases as: lowering the main cable, hitch, drag, placing of roadside trees, trip, stacking trees, displacement of the tractor and interruptions. Data analysis used was the variance analysis and Tukey test at 5% significance level, followed by a simple linear regression. The results demonstrated that the partial activity consumed the greater of the operational cycle time was passing the main cable in the trees, with 35.8% of the total time, unlike the less time spent were breaks in the field with about 4% of total operational time, having average productivity of cable variations from 10.2 to 115.3cc.m³.h-1, being totally linked to the variation distance extraction. Regression analysis it is observed that the productivity of cable logging in the mountainous region was influenced by the volume of wood beam, the operational cycle time and distance extraction. Keywords: Forest harvesting; aerial cables; operating income. DOI: http://dx.doi.org/10.14583/2318-7670.v02n04a09